Solve the system using substitution.

x = y − 6
y = 6 − 3x

A. (0, 6)
B. (6, 0)
C. (0, −6)
D. (−6, 0)

2 answers

well, geez -- how about, um, substituting?

You see that x = y-6, so substitute that into the other equation and you can then find y:

y = 6-3(y-6)
...
answer is A
Similar Questions
    1. answers icon 3 answers
  1. Solve the system of equations by SUBSTITUTION.6y+5x=8 x+3y=−7 (1 point) ​What would your equation look like after the first
    1. answers icon 1 answer
    1. answers icon 5 answers
  2. 1. Verify that (-4, 12) is the solution to the system.Show work to justify your answer 2x+y=5 -5x-2y=-6 2. Solve the system by
    1. answers icon 4 answers
more similar questions